EVALUASI USABILITY TERHADAP SIAM UNPRI MENGGUNAKAN METODE HEURISTIC EVALUATION DAN USER TESTING - br Bangun, Agita Putri; Octaviani, Vina; Pasaribu, Gres Audia; Harmaja, Okta Jaya (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
This study aims to assess the level of usability of the Student Academic Information System (SIAM) at Universitas Prima Indonesia (UNPRI) with a heuristic evaluation and user testing approach. Heuristic evaluation was conducted by three expert evaluators in the field of UI/UX and 21 problems were found during the trial process. Based on the results of heuristic evaluation testing, redesign and user testing of the redesign were carried out. Quantitative data obtained using the System Usability Scale (SUS) questionnaire, obtained a score of 80.5, which indicates that the redesigned system is in the “acceptable” category, but some improvements need to be made. Design improvement recommendations from these findings have been developed to improve the quality of system usage, especially SIAM UNPRI.